209Bi(N,TOT.) CROSS-SECTIONS FOR INCIDENT NEUTRON ENERGIES 0.01-400 eV - A. K. M. Moinul Haque MEAZE; Guinyun KIM
The neutron induced total cross-sections of 209Bi for the energies 0.01 - 400 eV were measured with the neutron time of flight (TOF) method at the pohang neutron facility (PNF), Korea. The PNF consists of a 100 MeV electron linear accelerator (LINAC), a water cooled Tantalum (Ta) target, 12.06 m TOF path length, four position automatic sample changer controlled remotely by the CAMAC data acquisitions systems, and a 6LiZnS(Ag) inorganic scintillator as a neutron detector. The distance from the water cooled Ta target to the sample changer is 5.4 m. To reduce the gamma flash originated from the neutron target we have employed a neutron-gamma separation system based on their different pulse shape. The sample was highly pure. The size of the sample 209Bi was 100 × 100 × 0.5 mm. In order to estimate the background and also to calibrate the energy we used notch filter of Cobalt (Co), Indium (In), and Cadmium (Cd) that has a large resonance peaks within our analyzed energy region. The area of the each samples of notch filter was 100 × 100 mm, and the thickness were 0.5 mm for Co and Cd; and 0.2 mm for the In. The transmission experiments were carried out on samples in and samples out method. The present measured values were compared with the others reported values and with the latest evaluated reaction data library ENDF/B-VII.0. The present measured neutron total cross-sections are generally in good agreement with the others experimental data and the evaluated data library.
Keywords: Physics; Nuclear physics